Performance Analysis of Commercial Banks in the Kingdom of Bahrain (2001-2015) - Iqbal Thonse Hawaldar; Lokesha Lokesha; K. Abhaya Kumar; Prakash Pinto; Sheila M. Sison (International Journal of Economics and Financial Issues, 2017)
Banking sector plays a leading role in financing a country's economic activities.  Its performance is crucial in determining a country's economic growth. This paper examines the performance of commercial retail banks (conventional and Islamic) in Bahrain and financial ratios were used for the period 2001-2015 on parameters such as profitability, liquidity, operating efficiency, capital adequacy and leverage. The empirical results revealed that conventional retail banks, except for Bahrain Development Bank, have consistent performance in ROA and ROE while among the Islamic retail banks, the performance of Kuwait Finance House is satisfactory in terms of profitability. The data also shows that all banks have satisfactory risk assets ratio. The commercial banks' profitability and capital adequacy as well as their profitability and efficiency are statistically correlated. There is a significant difference in the capital adequacy but no significant difference in profitability and liquidity was found among the listed commercial retail banks.